2018
DOI: 10.1186/s40168-018-0403-x
|View full text |Cite
|
Sign up to set email alerts
|

Apple endophytic microbiota of different rootstock/scion combinations suggests a genotype-specific influence

Abstract: BackgroundHigh-throughput amplicon sequencing spanning conserved portions of microbial genomes (16s rRNA and ITS) was used in the present study to describe the endophytic microbiota associated with three apple varieties, “Royal Gala,” “Golden Delicious,” and “Honey Crisp,” and two rootstocks, M.9 and M.M.111. The objectives were to (1) determine if the microbiota differs in different rootstocks and apple varieties and (2) determine if specific rootstock-scion combinations influence the microbiota composition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
106
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 42 publications
10
106
2
Order By: Relevance
“…2b; Additional file 1: Figure S2). This was consistent with microbiome study in Brassicaceae [24], sunflower [45] and Apple [46], where host genotypes have a stronger effect on fungal microbiota than bacteria. Unexpectedly, the microbial community of gramineous seeds of Avena sativa clustered far from Elymus sibiricus and Elymus dahuricus, and the bacterial community even clustered together with the Trifolium repens and Medicago sativa.…”
Section: Differences In Fungal Communities Across Grass Speciessupporting
confidence: 91%
“…2b; Additional file 1: Figure S2). This was consistent with microbiome study in Brassicaceae [24], sunflower [45] and Apple [46], where host genotypes have a stronger effect on fungal microbiota than bacteria. Unexpectedly, the microbial community of gramineous seeds of Avena sativa clustered far from Elymus sibiricus and Elymus dahuricus, and the bacterial community even clustered together with the Trifolium repens and Medicago sativa.…”
Section: Differences In Fungal Communities Across Grass Speciessupporting
confidence: 91%
“…The endophyte community in woody stems was less affected by cultivars when ‘Scifresh’ was included, with only total fungal and γ‐proteobacterial taxa shown to be different. Liu et al () found that cultivars with closer pedigree had more similar microbial communities than those with distantly‐related pedigrees. ‘Scifresh’ is a cross of ‘Braeburn’ and ‘Royal Gala’, and thus is intermediate between the two cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Also using DGGE, Patel and Archana () demonstrated culturable endophytic diazotrophic communities were similar in different plant tissues (leaf, stem and root) of cereal plants ( Poaceae ), which revealed their diverse but nonspecific colonization in cereal plants. Apple endophyte community was found to be associated with cultivar and cultivar‐rootstock combinations by Illumina‐based next‐generation sequencing, and cultivars with closer pedigree had more similar microbial communities than those with distantly related pedigrees (Liu et al ). Using terminal restriction fragment length polymorphism, Hirakue and Sugiyama () showed that resistance of apple cultivars to Alternaria leaf spot (caused by Alternaria mali ) was related to the fungal endophyte diversity in leaves.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of endophytic mycobiota of fruit trees can be diverse depending on the tree species [23]. Liu et al [31] suggested a genotype-specific influence of different rootstock/scion combinations on apple endophytic microbiota. Another study revealed limited geographic differentiation of fungal communities in apples trees, while a high diversity of fungal community structures was found in blackcurrant from different regions [32].…”
Section: Introductionmentioning
confidence: 99%